Influence of Aveiro Lagoon heavy metal contents in the adjacent continental shelf (Portugal) - Abrantes, I. (2005)
A chemical analysis of Al, Ca, Fe, Mg, Cu, Pb, Zn, Cr, Co, Ni and Cd was carried out in 22 surface sediment samples of the continental shelf and upper slope between Espinho and Aveiro (Portugal). To reduce the disturbing effects of grain size, all samples were size-normalized by wet sieving (<63 µm). The fine fraction was digested with concentrated acids and analyzed by flame atomic absorption spectrometry. The Al and heavy metal concentrations displayed a similar distribution pattern, decreasing seaward. Exceptions to this general pattern are Ca, Mg and Pb distributions. The Ca contents are related to carbonated biogenic particles that are very abundant in the outer shelf. Multivariate statistical analysis was applied to all data to assess the behaviour and sources of each element analyzed. The results from factor analysis showed that terrigenous supply (from Aveiro Lagoon flow, coastal erosion and littoral drift), grain size (clay) sorting and anthropogenic influences from Aveiro Lagoon are the major factors controlling spatial variations of chemical elements in the continental shelf between Espinho and Aveiro. Unusually high contents of Pb were found in the middle shelf off Furadouro, but we could not determine the possible source of this contamination.